Respuesta :

Answer:

In the equation for the exponential function, f(x) = P(1 + r)^x, the variable "r" represents the rate of change or the growth factor of the function. To find the value of "r" algebraically, we can use the following methods:

Logarithmic Differentiation: We can take the natural logarithm of both sides of the exponential equation and then differentiate with respect to x. This will give us an equation in terms of ln(f(x)) and x, and we can then solve for r by isolating it on one side of the equation.

Direct Substitution: We can substitute known values of x and f(x) into the exponential equation, and then solve for r by isolating it on one side of the equation.

By using the data. You can use the data and graph of the function to identify the rate of change, you can find the slope of the line in the graph, the slope represents the rate of change

It's worth noting that the value of r can be positive or negative, a positive value means that the function is increasing, and a negative value means that the function is decreasing.

Answer:

[tex]r=\left(\dfrac{y}{P}\right)^{\frac{1}{x}}-1[/tex]

Step-by-step explanation:

Given exponential function:

[tex]f(x)=P(1+r)^x[/tex]

Replace f(x) with y:

[tex]y=P(1+r)^x[/tex]

Divide both sides by P:

[tex]\dfrac{y}{P}=(1+r)^x[/tex]

Take natural logs of both sides:

[tex]\ln \left(\dfrac{y}{P}\right)=\ln (1+r)^x[/tex]

[tex]\textsf{Apply the power law}: \quad \ln x^n=n \ln x[/tex]

[tex]\ln \left(\dfrac{y}{P}\right)=x \ln (1+r)[/tex]

Divide both sides by x:

[tex]\dfrac{1}{x}\ln \left(\dfrac{y}{P}\right)=\ln (1+r)[/tex]

[tex]\textsf{Apply the power law}: \quad n \ln x=\ln x^n[/tex]

[tex]\ln \left(\dfrac{y}{P}\right)^{\frac{1}{x}}=\ln (1+r)[/tex]

Raise both sides to power of e:

[tex]\large\text{$e^{\ln \left(\frac{y}{P}\right)^{\frac{1}{x}}}=e^{\ln (1+r)}$}[/tex]

[tex]\textsf{Apply the power law}: \quad e^{\ln x}=x[/tex]

[tex]\left(\dfrac{y}{P}\right)^{\frac{1}{x}}=1+r[/tex]

Subtract 1 from both sides:

[tex]\left(\dfrac{y}{P}\right)^{\frac{1}{x}}-1=r[/tex]

Therefore, the equation to find r is:

[tex]r=\left(\dfrac{y}{P}\right)^{\frac{1}{x}}-1[/tex]